Teruk kūttāṭikaḷ taṉippatamākiya karnāṭaka nāṭaka alaṅkāra kītam - Cāraṅkapāṇi, Po (Caṇmukāṉanta Puttakacālai, 1981)
Songs in praise of Hindu deities, usually sung by the performers of the terukkūttu, Tamil folk drama.